Circulating Interleukin 6 and Albumin, and Infliximab Levels Are Good Predictors of Recovering Efficacy After Dose Escalation Infliximab Therapy in Patients with Loss of Response to Treatment for Crohn's Disease: A Prospective Clinical Trial. Issue 9 (September 2015) - Suzuki, Yasuo; Matsui, Toshiyuki; Ito, Hiroaki; Ashida, Toshifumi; Nakamura, Shiro; Motoya, Satoshi; Matsumoto, Takayuki; Sato, Noriko; Ozaki, Kunihiko; Watanabe, Mamoru; Hibi, Toshifumi
Abstract : Background: We aimed to clarify the efficacy, safety, and factors associated with remission on dose escalation in patients with Crohn's disease showing loss of response (LOR) to infliximab treatment of 5 mg/kg at 8-week intervals in a clinical trial. Methods: Thirty-nine patients with LOR to 5 mg/kg infliximab therapy started treatment with 10 mg/kg per 8 weeks. LOR was defined as both a Crohn's Disease Activity Index of ≥175 at 8 weeks after infusion of 5 mg/kg infliximab and a Crohn's Disease Activity Index increase of ≥50 from 4 to 8 weeks after infusion. Results: At week 8 after the first infusion of 10 mg/kg, median (95% confidence interval) reduction in Crohn's Disease Activity Index of 33 patients evaluated was 95.0 (70.0–134.0), meeting the primary endpoint. Remission rate at week 40 was 41% (16 of 39), with correlation noted between remission achievement and serum infliximab level ( P = 0.036). Univariate analysis revealed that "infliximab trough level ≥1 µg/mL, " "interleukin 6 level ⩽2.41 pg/mL, " and "albumin level ≥3.8 g/dL" before dose escalation were significantly associated with remission at week 40 ( P = 0.017, P = 0.011, and P = 0.019, respectively), and these variables were correlated with each other (all: P < 0.001). The cutoff infliximab level for remission was 0.42 µg/mL in receiver operating characteristic curve analysis. No adverse events related to dose escalation were observed. Conclusions: Doubling the infliximab dose safely led to remission in patients with Crohn's disease with LOR to 5 mg/kg treatment. Remission was associated with pre-escalation levels of infliximab, interleukin 6, and albumin. Our findings suggest that dose escalation while maintaining a certain level of infliximab is important in achieving remission. Abstract : Article first published online 24 July 2015.